Socioeconomic Inequalities and Life Expectancy in Newly Established Provinces: A Case Study in the Highland Papua - Navoleon, Alfaridho (Journal of Interdisciplinary Socio-Economic and Community Study, 2024)
The study aims to explore the relationship between socioeconomic inequalities and life expectancy in newly established provinces, specifically in Highland Papua. The initial hypothesis posits that socioeconomic inequalities, such as the Gini index and poverty rates, significantly impact public health. The analysis method employs the Pearson correlation test to examine the relationship between these variables. The results indicate no significant relationship between socioeconomic disparities and life expectancy at the specified level of significance. These findings underscore the complexity of factors influencing health, including access to health services, environmental conditions, and individual health practices. The implications of this discovery highlight the importance of a holistic approach to health policy design, focusing on public empowerment, intensive health education, cross-sectoral collaboration, and thorough policy evaluation. By integrating this approach, it is expected that overall public health will improve and existing health disparities will be reduced.